Green bonds under financial stress - Ichwan Ichwan; Taufiq C. Dawood; Zia Thahira; Wisnu Satria; Mirzatul Kadri (Journal of Economics Research and Policy Studies, 2026)
This study analyzed the relationship between financial stress and green bond issuance using a balanced panel of ten countries over the 2018 to 2023 period. A two-way fixed effects panel regression was employed to control for unobserved country specific and time specific factors. The findings showed that higher financial stress was associated with increased green bond issuance, indicating that green bond markets remained active during periods of financial pressure. GDP and domestic credit to the private sector also exhibited positive and statistically significant relationships with green bond issuance, highlighting the importance of macroeconomic capacity and financial intermediation. Inflation, by contrast, displayed a positive but statistically insignificant association. Additional analysis revealed no meaningful differences between advanced and non-advanced economies, and robustness checks confirmed the stability of the findings. Overall, the results suggested that green bonds represented a relatively resilient financing instrument under varying financial conditions and underscored the importance of supportive policy frameworks in fostering green bond market development.